Dithiafulvenyl-naphthalenediimide-based small molecules as efficient non-fullerene electron-transport layer for inverted perovskite solar cells - Dada B. Shaikh (2020)
Novel dithiafulvenyl (DTF)‐naphthalenediimide (NDI) derivatives DS1 and DS2 has been designed, synthesized and characterized. To replace the costly PCBM in inverted perovskite solar cells (PSCs), we here propose these materials. DS1 and DS2 were employed as electron transport layers (ETL) to fabricate inverted PSCs based on CH3NH3PbI3‐xClx. The best power conversion efficiencies (PCEs) of inverted PSCs based on DS1 and DS2 exhibit 9.6% and 11.4%, respectively. The difference in PCE values revealed that DS2 bearing two DTF moieties on NDI core could enhance the PCE compared to DS1 containing one DTF moiety. Our results suggest that NDI‐based small molecules could be employed as a promising ETL in inverted PSCs to achieve high efficiency.